Color stability evaluation of pigment extracted from hylocereus polyrhizus, clitorea ternatae and pandanus amaryllfolius as cosmetic colorants and premarket survey on customer acceptance on natural cosmetic product - N.N. Azwanida; Ma Sze Hui; Asrul Afandi Ab. Halim; Shamsul Mohamed; Zulhisyam Abdul Kari @ Abdullah; Amizi Ayob; Mohd Sukhairi Mat Rasat; Mazlan Mohamed (Universiti Malaysia Kelantan, 2015)
As public concern towards the long term effect of synthetic materials used in cosmetic formulations, such as the synthetic colorant, therefore natural ingredients are getting more preferred. In this research, evaluation of potential natural colorant extracted from H.polyrhizus, C.ternatae and P.amaryllfolius were investigated in terms of pigments stability against heat exposure. Pigments from each sample were exposed at different temperatures (30°C, 37°C, 40°C, 50°C, 60°C, 70°C, 80°C). Color intensities were measured at 517 nm and compared with control over a week to observe color changes and absorbance readings. Heat treatments were done to investigate the suitability of pigments to be incorporated as colorant in cosmetics products (lipstick) because the production of lipstick required high temperature to melt the ingredients. Pigments from H.polyrhizus showed to be most stable after heat treatment in comparison to C.ternatae and P.amaryllfolius. A premarket survey was done to investigate the customer acceptance on natural vs. synthetic products. Extracts from H. Polyrhizus (red), C.ternatae (blue) and P.amaryllfolius (green) were used to produce natural lipstick where matching synthetic colorant were used to produce another set of lipstick. An online survey was sent to 50 respondents all over the world from the age of 16-52 years old to investigate acceptance on the natural vs. synthetic product. Ranking test (Likert Scale) and hedonistic test were used to compare the best accepted product, color and pH. The consumer acceptance was investigated using the Ranking Test (Likert Scale) and Hedonic Scale test. At the end of the investigation, natural red lipstick was being chosen as the best preferred lipstick at 80% regarding its color and pH. All statistical analysis was done by SPSS and p value <0.05 was considered as significant. The finding suggested that natural colorant (red) was more preferred in comparison to synthetic colorant in cosmetic product based on its color and pH preferences. Thus, focus should be directed towards use of H.polyrhizus in cosmetic products due to higher stability and customer preferences.